2010
DOI: 10.1590/s0104-11692010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to breastfeeding cessation before 6 months

Abstract: This research aimed to identify the determinants of full breastfeeding (FBF) and any breastfeeding (ABF) cessation before 6 months, through a six-month follow-up of 248 mothers going a postpartum visit. Data were collected by personal interview during the first month and telephone interviews at four and six months postpartum. Coxs proportional hazards model was used. Not having previous ABF experience, previous ABF duration Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
18
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 15 publications
9
18
0
11
Order By: Relevance
“…3 Sex was not associated with malocclusion, as confirmed in previous studies. 6,25 Whereas a number of authors argue that children with greater purchasing power and those whose mothers have a lower schooling level are more likely to develop malocclusion due to greater access to and frequency of pacifier use, 29,30 no significant associations were found in the present study between socioeconomic indicators and malocclusion, in agreement with findings reported in previous studies. 6,9 It seems that another factor unassociated to social class has occurred, namely the greater participation of women in the workforce, with a consequent reduction in breastfeeding and greater susceptibility to the adoption of nonnutritive sucking habits.…”
Section: Resultssupporting
confidence: 91%
“…3 Sex was not associated with malocclusion, as confirmed in previous studies. 6,25 Whereas a number of authors argue that children with greater purchasing power and those whose mothers have a lower schooling level are more likely to develop malocclusion due to greater access to and frequency of pacifier use, 29,30 no significant associations were found in the present study between socioeconomic indicators and malocclusion, in agreement with findings reported in previous studies. 6,9 It seems that another factor unassociated to social class has occurred, namely the greater participation of women in the workforce, with a consequent reduction in breastfeeding and greater susceptibility to the adoption of nonnutritive sucking habits.…”
Section: Resultssupporting
confidence: 91%
“…A similar finding was obtained in a study on European infants, where the proportion of mothers offering EB in the first, third and sixth month was 67.7% (n = 168), 58.1% (n = 144) and 12.5% (n = 31), respectively 14 . Among the factors discussed, it was verified that the mother's age profile was similar to that found in other studies, mostly between 20 and 30 years 9,15 .…”
Section: Resultssupporting
confidence: 87%
“…Corroborating with the findings of this study, the experience of previous gestation is described as a protective factor against adherence to breastfeeding. The greater the number of pregnancies, the greater the experience of the mothers and, therefore, the longer the duration of breastfeeding for the next children 14 . Not having breastfed a child previously is the variable with the highest independent risk for abandonment of EB or complete cessation of breastfeeding, followed by breastfeeding for four months or less.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data show a relationship between use of pacifiers and interruption of exclusive breastfeeding 8 or abandonment of breastfeeding 23 . However, its mechanism of action remains unclear.…”
Section: Resultsmentioning
confidence: 99%